The dissemination of information - Rowley, J. E.; Turner, Christopher Mark Dirham (London : Deutsch, 1978)
The authors begin with an outline of the nature and use of information and follow this with a general discussion of information services and a justification for the existence of such services.
Includes bibliographical references and index.
ne 23/01/2019
Loans
Keywords: Information services; Information science